Incidence and distribution of Sweetpotato viruses and their implication on sweetpotato seed system in Malawi - Mbewe, W.; Mtonga, A.; Chiipanthenga, M.; Masamba, Kingsley; Chitedze, G.; Pamkomera, P.; Gondwe, E.; Mwenye, O.; Chipungu, Felistus P. (Springer, 2021)
A survey was carried out in 19 districts to investigate the prevalence and distribution of sweetpotato virus disease (SPVD) and its implication on the sustainability of clean seed system in Malawi. A total of 166 leaf samples were collected and tested for the presence of 8 viruses using nitrocellulose membrane enzyme-linked immunosorbent assay (NCM-ELISA). SPVD foliar symptoms were observed in 68.42% of the surveyed districts. There were significant variations in disease incidence and severity (p < 0.001) among districts, with the highest incidence in Mulanje (28.34%). Average SPVD severity score was 3.05. NCM-ELISA detected sweet potato feathery mottle virus (SPFMV, 30.54%), sweet potato mild mottle virus (SPMMV, 31.14%), sweet potato mild speckling virus (SPMSV, 16.17%), sweet potato C-6 virus (SPC6V, 13.77%), sweet potato chlorotic stunt virus (SPCSV, 22.16%), sweet potato collusive virus (SPCV, 30.54%), sweet potato virus G (SPVG, 11.38%), cucumber mosaic virus (CMV, 7.78%) either in single or mixed infections. Data from this study indicate a significant SPVD occurrence in the country, and the consequence implications towards national sweetpotato seed system.